1993
DOI: 10.1046/j.1365-2648.1993.18122008.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care: situations of ethical difficulty

Abstract: Twenty enrolled nurses (ENs), 20 registered nurses (RNs) and 20 physicians working in intensive care in northern Sweden narrated 255 stories about their experience of being in ethically difficult care situations. The ENs' stories mainly concerned problems relating to relationship ethics, the stories narrated by the physicians mainly concerned problems relating to action ethics, while the RNs' stories gave equal attention to both kinds of problems. The most common theme of both the RNs' and the physicians' stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 15 publications
6
50
0
5
Order By: Relevance
“…2 Nurses working in intensive care units, other hospital wards and in community health care have reported what they perceive as an overuse of life-sustaining treatments for patients with a poor prognosis. [3][4][5][6][7][8] Studies have shown contradictory findings regarding the opinions expressed by nurses concerning their wish to be involved in decision making as opposed to their actual behaviour. In some studies nurses have indicated that they have felt left out of decision making [9][10][11][12][13][14] and that they want more influence.…”
Section: Introductionmentioning
confidence: 99%
“…2 Nurses working in intensive care units, other hospital wards and in community health care have reported what they perceive as an overuse of life-sustaining treatments for patients with a poor prognosis. [3][4][5][6][7][8] Studies have shown contradictory findings regarding the opinions expressed by nurses concerning their wish to be involved in decision making as opposed to their actual behaviour. In some studies nurses have indicated that they have felt left out of decision making [9][10][11][12][13][14] and that they want more influence.…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous research has shown that the experience of ethical difficulties varies depending on cultural differences 7 and different professions. 8 In pediatric care, common ethical issues include what procedures to adopt when children are unwilling to cooperate and complex decisions about life and death. 5,9 Pediatric care is special because of children's need to have a parent/guardian present and participating in caring procedures and decisions but also because of the rights of children for respect of their views and wishes, according to their developmental level and growing autonomy.…”
mentioning
confidence: 99%
“…The conflict between promoting the patient's quality of life and keeping him or her alive, which was a common theme in the previously noted interviews, 5,6,13 was hardly mentioned by the retired nurses. This is probably because the possibilities of keeping severely ill patients alive for long periods of time is a new feature in care.…”
Section: Retired Nurses' Stories Of Ethically Difficult Situations 131mentioning
confidence: 89%
“…1 One way of disclosing the experience is to analyse people's stories about being in concrete situations. 2 Analyses have previously been made of Norwegian registered nurses' stories about being in ethically difficult care situations in oncological and medical care, 3,4 and nurses in oncological, medical and surgical care, 5 physicians, registered nurses and enrolled nurses in intensive care, 6 and physicians, registered nurses and enrolled nurses in surgical care, 7 in Sweden. In these studies, the registered nurses revealed a nursing perspective regarding ethics (i.e.…”
Section: Introductionmentioning
confidence: 99%